Ben Cao Gang Mu. - Li, Shizhen (University of California Press, 2024)
Volume I is divided into two parts. Part B of volume I in the Ben cao gang mu series offers a translation of portions of chapter 3 and the complete chapter 4, devoted to pharmaceutical drugs for diseases. This volume is a continuation of volume I, part A. The first portion of chapter 3 is found in part A. The Ben cao gang mu is a sixteenth-century Chinese encyclopedia of medical matter and natural history by Li Shizhen.
Keywords: Medicine, Chinese -- History -- 16th century.; Medicine, Chinese -- Early works to 1800.; Materia medica -- China -- Early works to 1800.; Drugs, Chinese Herbal; Médecine chinoise -- Ouvrages avant 1800.; Matière médicale -- Chine -- Ouvrages avant 1800.; Médecine chinoise -- Histoire -- 16e siècle.; MEDICAL / Acupuncture.; Materia medica; Medicine, Chinese; China; Early works